Ozone over McMurdo Station, Antarctica, austral spring 1986 - Altitude profiles for the middle and upper stratosphere - Connor, Brian J.; Barrett, J. W.; Parrish, A.; Solomon, P. M.; De Zafra, R. L. (1987)
In the austral spring of 1986, a program of measurements of the ozone altitude profile (for the z values between 25 and 55 km), relevant to an understanding of the ozone hole, was conducted at McMurdo Station, Antarctica. The measurements were performed using ground-based millimeter-wave spectrometry. It was found that the ozone mixing ratio peaked at altitudes ranging from 28 to 34 km, with peak values between 5 and 9 ppm by volume. During the period between September 12 and October 29, the ozone mixing ratio decreased, with great variability, by about 15 percent at 25 km, with no significant decrease at higher altitudes. The observation of the depletion occurring only below 25 km is consistent with ozone-sonde observations during previous years.